An Ecosystem-Based Approach to Climate-Smart Agriculture with Some Considerations for Social Equity - International Rice Research Institute; International Institute of Rural Reconstruction (International Rice Research Institute, 2022)
The International Institute of Rural Reconstruction (IIRR) in collaboration with the International Rice Research Institute (IRRI), developed discussion briefs that would further enhance the knowledge of ClimBeR’s stakeholders on resilience, inclusiveness and women empowerment in climate change adaptation in the Philippines. This brief discusses social equity in the context of ecosystem-based approaches.